The Influence of Financing, Social Finance, and GCG On Islamic Bank Financial Stability in Indonesia - Mahendra, Taufik Riza; Hanafi, Syafiq Mahmadah (Jurnal Magister Ekonomi Syariah, 2025)
The current development of banking has become a benchmark in determining Indonesia's economic growth. The benchmark for determining the development of banking can be seen from several conditions of the bank's financial performance. In maintaining its business activities, Islamic banks are required to uphold the stability of their institutions. This study examines and analyzes the influence of financing, corporate social responsibility (CSR), and audit committees on the financial stability of Islamic commercial banks in Indonesia. The method used in this study is quantitative-descriptive. The sample in this study used purposive sampling with samples from 2015-2022 in Indonesia. Thus, a sample of 56 data points was obtained. Based on the findings of this study, financing has a positive effect on the financial stability of Islamic commercial banks. This is because sound financing practices serve as a key mechanism for Islamic banks to generate profits and maintain financial stability. Corporate Social Responsibility (CSR) also has a positive impact on financial stability, as the implementation of CSR initiatives enhances the bank's public image and builds customer trust, thereby encouraging customers to choose Islamic banks. Furthermore, the audit committee significantly influences financial stability due to its crucial role in ensuring that the bank’s operations comply with prevailing regulations and governance standards.